2019
DOI: 10.1186/s12885-018-5227-3
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node positivity in different early breast carcinoma phenotypes: a predictive model

Abstract: BackgroundA strong correlation between breast cancer (BC) molecular subtypes and axillary status has been shown. It would be useful to predict the probability of lymph node (LN) positivity. Objective: To develop the performance of multivariable models to predict LN metastases, including nomograms derived from logistic regression with clinical, pathologic variables provided by tumor surgical results or only by biopsy.MethodsA retrospective cohort was randomly divided into two separate patient sets: a training s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 28 publications
6
25
0
2
Order By: Relevance
“…Lu et al confirmed that the lowest probability of node metastasis was in estrogen receptor (ER) − /HER2 − cancers (31). Similarly, in our study, triple negative tumors had the lowest probability of LNM, while HR − /HER2 + tumors had the highest probability, which was in agreement with the findings of previous study (26). Reyal et al hypothesized that the process of axillary LNM was mainly related to intrinsic biological characteristics in the ER − /HER2 − breast cancer subgroup, while tumor size, growth rate and lympho-vascular invasion were the main determinants in both the ER positive or the HER2 positive breast cancer subgroups (32).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Lu et al confirmed that the lowest probability of node metastasis was in estrogen receptor (ER) − /HER2 − cancers (31). Similarly, in our study, triple negative tumors had the lowest probability of LNM, while HR − /HER2 + tumors had the highest probability, which was in agreement with the findings of previous study (26). Reyal et al hypothesized that the process of axillary LNM was mainly related to intrinsic biological characteristics in the ER − /HER2 − breast cancer subgroup, while tumor size, growth rate and lympho-vascular invasion were the main determinants in both the ER positive or the HER2 positive breast cancer subgroups (32).…”
Section: Discussionsupporting
confidence: 93%
“…We also found that the risk of LN involvement decreases with women's age from youngest to oldest. Younger patients (age <40 years old) were more likely to have LNM than other age groups, and same results were shown in other researches (14,26). Moreover, increasing tumor histologic grade was significantly associated with an increased risk of LNM.…”
Section: Discussionsupporting
confidence: 84%
“…For patients in the TNBC subgroup having small tumor burdens, the average number of FN ALNs was more then 2, which might be due to only 1 (5.9%) patient developing ALN metastasis. Similar to our study, Lu et al published that the lowest probability of node metastasis was for ER-/ HER2-tumors [39], and Houvenaeghel et al also reported TNBC had the lowest probability of node metastasis [40]. Owing to a high NPV and small possibility of ALN metastasis, ALN staging by MRI is still promising in the TNBC group.…”
Section: Discussionsupporting
confidence: 88%
“…On the basis of the state-of-art, most works propose non-sentinel lymph node status predictive models by using features of a different nature, including nomograms of clinical and pathologic variables [ 33 , 34 , 35 , 36 , 37 ]. On the other hand, the literature is poor in studies aimed at the development of sentinel lymph nodes predictive models [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%